A Case of Kikuchi's Disease Without Cervical Lymphadenopathy - Shinya Tomori; Seigo Korematsu; Taichi Momose; Yasuko Urushihara; Shuji Momose; Koichi Moriwaki (Hindawi Limited, 2022)
Background. Kikuchi's disease with only extracervical lymphadenopathy is rare. Case Presentation. A 15-year-old male has presented with a fever lasting more than 1 week and right axillary lymphadenopathy. An axillary lymph node biopsy revealed coagulation necrosis, nuclear decay products, infiltration of histiocytes, and enlarged lymphocytes; he was diagnosed with Kikuchi's disease. The only four adult patients with Kikuchi's disease presenting without cervical lesions have been previously reported. Conclusion. This is the only pediatric case of Kikuchi's disease presenting without cervical lymphadenopathy. Kikuchi's disease should be included in the differential diagnosis even in cases of extracervical lymphadenopathy alone.